Testing for the existence of an S-curve in Croatia, Hungary, and Slovenia: A Note - Aleksandar Vasilev (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2010)
In this note we check for the existence of an S-surve for Croatia, Hungary and Slovenia. We interpret the results in the spirit of the business cycle literature. Compare institutions, fiscal/monetary policy, whether they had currency/banking crises within the sample, how much they trade trade and how are those countries similar or different compared to the evidence from international data.
Keywords: A1; 330; S-curve; REER